Shade and drought increase fungal contribution to partially mycoheterotrophic terrestrial orchids Goodyera pubescens and Tipularia discolor - McCormick, Melissa K.; Good, Kerry L.; Mozdzer, Thomas J.; Whigham, Dennis F. (Frontiers in Ecology and Evolution, 2022)
Many photosynthetic plants supplement photosynthetic carbon with fungal carbon, but the mechanisms that govern dependence on mycoheterotrophic carbon are poorly understood. We used exclusion shelters to manipulate water and light availability to plants of the terrestrial orchids Goodyera pubescens and Tipularia discolor. We tracked changes in δ13C from photosynthesis and δ15N acquired from soil-derived inorganic nitrogen versus mycoheterotrophy, along with direct measures of photosynthesis in T. discolor. We hypothesized that shade would increase dependence on mycoheterotrophy compared to reference plants, while drought would decrease both photosynthesis and the abundance of potential mycorrhizal fungi. Drought and shade enriched 13C and 15N in both G. pubescens and T. discolor, compared to control plants, indicating increased fungal contribution to orchid tissues. Physiological measurements of T. discolor leaves showed that dark respiration, water use efficiency, and relative electron transport rate did not vary significantly, but shaded plants had greater quantum efficiency, suggesting they were light-limited. Light saturated photosynthesis of T. discolor leaves was lower in both shaded and drought-treated plants, indicating lower photosynthetic capacity, and likely greater dependence on mycoheterotrophy and corresponding enrichment in 13C and 15N. This study documented changes in orchid dependence on fungal carbon in response to manipulated environmental conditions. Both shade and drought increased the dependence of both orchids on mycoheterotrophically-derived carbon and nitrogen.